Antibacterial activity and mechanism of Chuzhou chrysanthemum essential oil. (September 2018) - Cui, Haiying; Bai, Mei; Sun, Yanhui; Abdel-Samie, Mohamed Abdel-Shafi; Lin, Lin
Graphical abstract: Highlights: CCO exhibited antibacterial activity against both gram-positive and gram-negative bacteria. The influence of CCO on the oxidative respiratory metabolism of bacteria was studied. DNA topoisomerase inhibition assay was carried out to determine the antibacterial mechanism. Antibacterial mechanism of CCO was successfully explained from the molecular level. Abstract: Chuzhou chrysanthemum is well-known in China and has been used to make tea over centuries. However, neither integrated background about the antibacterial activity nor the antibacterial mechanism of Chuzhou chrysanthemum oil (CCO) is available. SDS-PAGE analysis, oxidative respiratory metabolism measurement and the DNA topoisomerase activity were employed to investigate the antibacterial mechanism of CCO. CCO could lead to the leakage of proteins of E. coli and S. aureus cells, and the protein contents in E. coli and S. aureus were dropped by 47.21% and 36.44% respectively after CCO treatment. SDS-PAGE results confirmed the disruptive action of CCO on cytoplasmic membrane of bacteria. CCO could affect the Hexose Monophophate Pathway of E. coli and the Embden-Meyerhof-Parnas Pathway of S. aureus . Furthermore, the result of DNA topoisomerase inhibition assay showed that the activity of topoisomerase I and topoisomerase II could be both inhibited by CCO treatment.